Search for new physics with long-lived particles decaying to photons and missing energy in pp collisions at root s=7 TeV - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Eroe, J; Fabjan, C; Friedl, M; Fruehwirth, R; et al. (2012)
A search is performed for long-lived neutral particles decaying into a photon and invisible particles. An example of such a signature is the decay of the lightest neutralino with nonzero lifetime into a gravitino and a photon in gauge-mediated supersymmetry, with the neutralino as the next-to-lightest supersymmetric particle and the gravitino as the lightest. The search uses events containing photons, missing transverse energy, and jets. The impact parameter of the photon relative to the beam-beam collision point can be reconstructed using converted photons. The method is sensitive to lifetimes of the order of 0.1 to 1 ns. The data sample corresponds to an integrated luminosity of 2.23 fb-1 in pp collisions at √s=7 TeV, recorded in the first part of 2011 by the CMS experiment at the LHC. Cross-section limits are presented on pair production for such particles, each of which decays into a photon and invisible particles. The observed 95% confidence level limits vary between 0.11 and 0.21 pb, depending on the neutral particle lifetime.[Figure not available: see fulltext.] © 2012 CERN for the benefit of the CMS collaboration.